The Influence of Social Media Representations in the Formation and Maintance of Norms Ethics for Unesa Social Science Students - Nathan, Aloisius; Mohammad Zaheer Azimi; Naufal Rizki Ahmad Hanafi; Firman Hidayah; Saiful Amin; Nasrulloh Muzaki (Universitas Negeri Surabaya, 2025)
The Social media has become an integral part of everyday life, especially for the younger generation, including students. As a platform that allows easy interaction and sharing of information, social media has a significant impact on the formation and maintenance of norms and ethics among students. This study aims to analyze how social media representation influences the norms and ethics of students in the Social Sciences Education Study Program (IPS) at Universitas Negeri Surabaya (UNESA). The study used a qualitative approach with interview and literature study methods. The results of the study indicate that social media contributes to the formation of social norms, providing space for students to express themselves and strengthen social relationships. However, dependence on social media also has negative impacts, such as adverse effects on mental health and behavior. Social media plays an important role in building ethical awareness through informative content and positive digital communities. This study concludes that social media has a dual role as a tool to strengthen norms and ethics, as well as a new challenge in the digital life of UNESA IPS students. Digital literacy and critical awareness are needed to optimize the benefits of social media while minimizing its impacts.